Liquid biopsy in the diagnosis of HPV DNA in breast lesions. (February 2018) - Carolis, Sabrina De; Pellegrini, Alice; Santini, Donatella; Ceccarelli, Claudio; De Leo, Antonio; Alessandrini, Federica; Arienti, Chiara; Pignatta, Sara; Tesei, Anna; Mantovani, Vilma; Zamagni, Claudio; Taffurelli, Mario; et al.
Aim: HPV DNA has never been investigated in nipple discharges (ND) and serum–derived extracellular vesicles, although its presence has been reported in ductal lavage fluids and blood specimens.Materials & methods: We analyzed 50 ND, 22 serum-derived extracellular vesicles as well as 51 pathologic breast tissues for the presence of 16 HPV DNA types.Results: We show that the presence of HPV DNA in the ND is predictive of HPV DNA-positive breast lesions and that HPV DNA is more represented in intraductal papillomas. We also show the presence of HPV DNA in the serum-derived extracellular vesicles.Conclusion: Our data supports the use of liquid biopsy to detect HPV DNA in breast pathology.